Visual Maturation at Term Equivalent Age in Very Premature Infants According to Factors Influencing Its Development - Wirth, Maëlle; Naud, Aurélie; Schmitt, Emmanuelle; Clerc-Urmès, Isabelle; Hascoët, Jean-Michel (Frontiers in Physiology, 2018)
Introduction: Visual impairment is a concern in premature infants as perinatal factors may alter maturation during visual development. This observational study aimed at evaluating visual maturation at term equivalent age and factors associated with impaired visual maturation. Methods: Infants born before 32 weeks’ gestation were evaluated with routine brain MRI, visual acuity, refraction, fundus, and clinical eye examination. Environmental factors were collected from infant’s files. Results: Fifty-four infants (29.5 ± 1.7 weeks’ gestation, birth weight 1194 ± 288 g) were studied at term equivalent age. Visual acuity was higher in premature infants at term equivalent age than in a reference publication with the same method in term newborns at birth (1.54 ± 0.67 vs. 0.99 ± 0.40 cycles/degree, p = 0.008). In multivariate analysis, abnormal brain MRI was the only factor associated with visual acuity (r2= 0.203; p = 0.026). Incomplete retinal vascularization was observed in 29/53 of infants at term equivalent age and associated with MRI abnormalities of the posterior fossa (p = 0.027) and larger refractive sphere difference between both eyes (1.2 ± 0.8 vs. 0.6 ± 0.4 diopters; p = 0.0005). Retinopathy of prematurity was associated with indices of smaller cerebral volume (p = 0.035). Conclusion: Higher visual acuity in premature infants at term equivalent age than in term newborns at birth may be related to longer visual experience from birth. Lower visual acuity was correlated with abnormal MRI in preterm infants at term equivalent age.